Análise biomecânica e funcional de indivíduos com osteoartrite de quadril - Melo, Cristiane de Sousa (Universidade Federal de São Carlos, 2024)
Hip osteoarthritis (OA) is an inflammatory and degenerative joint disease. Clinically, individuals with hip OA may exhibit biomechanical alterations during gait, such as pelvic instability and trunk inclination, in addition to negative impacts like difficulties in performing daily activities and the presence of pain. During the execution of certain functional tasks, especially those requiring single-leg support, individuals with hip OA may adopt specific strategies to reduce the demand on hip abductor muscles and to alleviate pain, such as ipsilateral trunk inclination and pelvic tilt toward the affected side. However, the relationship between these alterations and other activities beyond gait remains unclear. More specifically, the association between changes in muscle strength of other muscle groups, such as hip flexors and extensors, and the electrical activity of the rectus femoris in the presence of hip OA is not well understood, particularly in relation to functional capacity in individuals with early and moderate stages of the disease. To address these issues, two studies were conducted. The first study aimed to determine, through logistic regression models, whether the presence of alterations such as poorer performance in functional tasks, reduced muscle strength of hip flexors and extensors, and changes in the electrical activity of the rectus femoris could identify the presence of hip OA. A binomial logistic regression was used to analyze these data in Python. A total of 64 individuals were included: 32 with unilateral hip OA (56.28±8.71 years) and 32 asymptomatic individuals without hip OA (53.49±8.72 years), of both sexes. The nine models of combinations used (combinations of concentric and eccentric hip flexor muscle strength, concentric hip extensor strength, rectus femoris electrical activity during concentric and eccentric flexion, along with the three functional tests: the 30-second sit-to-stand test, the 40-meter fast walk, and the stair climb test) were able to detect the presence of OA, with the three functional tests being superior in detecting hip OA. The second study aimed to evaluate functional capacity and the step-down task in the frontal plane, assessing whether individuals with hip OA adopt trunk and pelvic inclination strategies during this task, at which phase(s) of the step-down these occur, and analyzing the behavior of other lower limb joints by evaluating joint angles of the hip, knee, and ankle, hip and knee joint moments, and ground reaction force. This study included 26 individuals: 13 with a diagnosis of unilateral hip OA (51.46±7.46 years) and 13 asymptomatic individuals without a diagnosis of hip OA (54.38±6.46 years), of both sexes. In performing the functional tests of stair climbing and descent, the 40-meter fast walk test, and the 30-second sit-to-stand test, volunteers with hip OA showed poorer performance compared to the control group (p<0.001). Greater ipsilateral pelvic inclination was found in individuals with hip OA during the controlled descent phase compared to the control group (p=0.033). Additionally, individuals with hip OA took longer to complete this phase compared to the control group (p=0.039). This thesis concludes that even in the early stages of hip osteoarthritis, individuals exhibit functional alterations compared to asymptomatic individuals, with the recommended functional tests for evaluating this population being effective in detecting the presence of hip OA.
Biomechanical and functional analysis of individuals with hip osteoarthritis
Keywords: Osteoartrite; Capacidade funcional; Biomecânica; Força muscular; Eletromiografia; Fisioterapia; Osteoarthritis; Functional capacity; Biomechanics; Muscle strength; Electromyography; Physiotherapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL